Electrochemical synthesis of nanostructured TiO2 thin films: surface characterization (2015)
This work describes the electrochemical synthesis of nano-structured TiO2 films on titanium substrates in mixed water-ethylene glycol solutions containing HF or NH4F. The major electrolysis variables such as cell voltage, electrolyte composition, and synthesis time affect the morphology of the films. While films with irregular morphologies were attained in acidic media, films showing regular nanotubular structures were attained under neutral pH conditions. The length of the tubes, the tube diameter and other features heavily depend on the content of NH4F in the electrolysis medium and the time of the reaction. The presence of water influences the formation of ribs around the tubes and of irregular deposits on the tubes mouth. Increasing the cell voltage decreases the thickness of the tube walls. If the electrolysis time is sufficiently large, the internal walls of the tube break open and the interior of the films exhibit a cave-like structure. XRD analysis shows that the films prepared at room temperature are amorphous bur crystalline anatase and rutile structures develop upon annealing in the temperature range between 300 and 700 °C.